(untitled) (Bangladesh Journal of Medical Education, 2017)
Background: Thesis work is an integral part of postgraduate medical education. It serves as the first stepping stone into scientific writing. But during research work, students and supervisors face various prob-lems. A number of research works has been conducted in different parts of the world on this issue. Some of the problems are candidate related and some of them are supervisor related. In Bangladesh, no re-search work has been done to find out the problems faced by the students and supervisors during thesis work. Once the prob-lems are identified, we can find ways and means to solve those problems as much as possible. Thus the students as the primary group will be benefitted from the results of this study and the supervisors will gain in-sights and will be able to lighten the prob-lems. Method: A cross sectional descriptive study was conducted in 20 different medical colleges and institutes in Bangladesh. A total of 133 postgraduate students, 46 supervisors participated in the study. Purposive sampling technique was used. Two pretested semi-structured questionnaire were used (one for students and one for supervisors) to collect data and data analysis was done using SPSS version 19. Results: The problems in general identified were lack of students’ knowledge, experience, commitment in thesis works, time constraint, excess workload, lack of fund, inadequate and irregular meeting with supervisors. Institute related problems were inadequate guidance and resources of the institute, absence of research cell and for-mats of thesis writing in the institute and inadequate cooperation from the institute. Conclusion and recommendation: The pre-sent study revealed that lack of knowledge, lack of experience, lack of fund and lack of regular meetings with supervisor were found the most important general prob-lems. Lack of research project and lack of resource were found the most common problems related to the institute. The rec-ommendations made were- research meth-odology and biostatistics should be incorporated in undergraduate and postgraduate curriculum, regular practical workshops on research methodology and biostatistics for the students and the supervisors, provision of adequate fund for academic thesis works, arrangement of adequate research facilities and resources in all institutes/universities conducting postgraduate courses, introduction of checklist and meeting schedule to be used both by supervisors and students during thesis works. Bangladesh Journal of Medical Education Vol.8(1) 2017: 22-27